Worldwide burden of gastric cancer in 2010 attributable to high sodium intake in 1990 and predicted attributable burden for 2030 based on exposures in 2010 - Peleteiro, B (2016)
Assessing the impact that patterns of Na intake may have on gastric cancer will provide a more comprehensive estimation of Na reduction as a primary prevention approach. We aimed to estimate the proportion of gastric cancer cases that are attributable to Na intake above the recommendation by the WHO (≤2 g/d) throughout the world in 2010, as well as expected values for 2030. Population attributable fractions (PAF) were computed for 187 countries, using Na intakes in 1990 and 2010 and estimates of the association between Na intake and gastric cancer, assuming a time lag of 20 years. Median PAF ranged from 10·1% in low to 22·5 % in very high Human Development Index (HDI) countries in men (P<0·001) and from 7·2 to 16·6 %, respectively, among women (P<0·001). An increase in median PAF until 2030 is expected in most settings, except for countries classified as low HDI, in both sexes. High Na intakes account for a large proportion of gastric cancer cases, and proportions are expected to increase in almost all of the countries. Intensified efforts to diminish Na intake in virtually all populations are needed to further reduce gastric cancer burden.